PENGARUH PERANG DAGANG AMERIKA SERIKAT DAN TIONGKOK TERHADAP INDEKS HARGA SAHAM GABUNGAN INDONESIA DI BURSA EFEK INDONESIA - Silfia Lintang Laily; Noor Shodiq Askandar; Junaidi Junaidi (e_Jurnal Ilmiah Riset Akuntansi, 2022)
This study aims to determine the effect of the trade war between the United States and China on the Indonesian Composite Stock Price Index. This type of research is quantitative. This research is an event study with purposive sampling method. The data used in this study is secondary data taken from www.idx.com and www.yahoofinance.com. The data was processed using the Kolmogorov-Smirnov test and paired sample t-test using SPSS version 16. The results showed that there were significant differences in the Composite Stock Price Index or IHSG during and after the trade war between the United States and China. This is indicated by the Asymp value. Sig (2-tailed) of 0.000 > α0.05.Keywords: Trade war, composite stock price index.